Extraction of Zn(II) from aqueous hydrochloric acid solutions into Alamine 336-m-xylene systems. Modeling considerations to predict optimum operational conditions - SAYAR, NİHAT ALPAGU (ELSEVIER, 2007)
Extraction of Zn(II) from its aqueous hydrochloric acid solutions into Alamine 336-m-xylene systems was studied. Extraction data were obtained with three different initial metal concentrations of 3, 7 and 15 g L-1 each at aqueous phase acidic molarities of 1, 5 and 10 mol L-1. It was observed that the increase in acidic molarity slightly increases the extractability of Zn(II). Alamine 336-m-xylene mixtures were found promising organic solvent systems for the Zn(II) extraction from aqueous media. 2-D, 3-D and 4-D mathematical model equations simulating metal extractability in terms of organic phase Alamine volume content, aqueous phase acidic molarity and initial metal concentration were developed. 4-D model equation was used to develop a performance index function in order to optimize the principal key inputs of the extraction operation. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: solvent extraction; Zn(II); modeling, simulation and optimization of extraction operations; LIQUID-LIQUID-EXTRACTION; DI(2-ETHYLHEXYL) PHOSPHORIC-ACID; SOLVENT-EXTRACTION; SULFATE-SOLUTIONS; CHLORIDE SOLUTIONS; CARBOXYLIC-ACIDS; ZINC EXTRACTION; SEPARATION; RECOVERY; NICKEL